PENDAFTARAN TANAH DENGAN ALAS HAK JUAL BELI DI BAWAH TANGAN PADA PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) (Studi Pada Kantor Pertanahan Kabupaten Lima Puluh Kota) - Donald Andrean (LPPM Universitas Ekasakti Padang, 2020)
In civil law, land is included in registered objects. Therefore ownership of land rights must be registered, for legal certainty. Land registration is regulated in PP No. 24 of 1997 concerning Land Registration. However, there are still many lands that have not been registered, to overcome this the government has issued a comprehensive systematic land registration program (PTSL) based on Minister of Agrarian Regulation No. 6 of 2018. The aim of this program is to provide legal certainty and legal protection for land rights owned by the community. The Complete Systematic Land Registration Program (PTSL) provides an opportunity for people who have not registered their land that is located throughout Indonesia in one village or village area. As in the Lima Puluh Kota Regency, there are still many lands that have not been registered, the people obtained them from buying and selling under their hands.The formulation of the problem in this thesis is firstly how is the land registration procedure with the basis of under-selling rights of purchase under the complete systematic land registration program (PTSL) at the fifty-city district land office ?; second, what are the obstacles in the implementation of land registration on the basis of the right to buy and sell under the complete systematic land registration program (PTSL) at the fifty-city district land office? The specification of this research is analytical descriptive, with a normative juridical approach, which is supported by an empirical juridical approach. The data used are secondary data as primary data and primary data as support, which are collected through literature studies and field studies with interview techniques. The data is then analyzed qualitatively and presented in a qualitative descriptive form. The results of the research and discussion of this thesis can be concluded that the procedure of land registration with the basis of the rights under the hand in the PTSL program in fifty cities is carried out with the stages of planning, location determination, preparation, formation and establishment of the PTSL adjudication committee and task force, counseling, physical data collection and collecting juridical data, researching juridical data for proving rights, announcing physical and juridical data and ratifying it, affirming conversion, recognizing rights and granting rights, accounting for rights, issuing certificates of land rights, documenting and submitting the results of activities and reporting.